2011
DOI: 10.1073/pnas.1018806108
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Seth et al.: DNAX accessory molecule-1 (DNAM-1) plays an important role in alloreactive CD8 + T cells responsible for the exacerbation of acute graft-versus-host disease

Abstract: We appreciate the comments of Seth et al.(1), because they provide an important finding that is supplementary to our paper (2). They show that recipient mice deficient in CD155 (Cd155 −/− mice), a ligand for DNAM-1 (DNAX accessory molecule-1, CD226), exhibited shorter rather than longer survival than WT mice after bone marrow transplantation (BMT) with full MHC disparity. They also show that donor CD4 + , but not CD8 + , T cells were responsible for the poor survival of the recipient Cd155 −/− mice, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…We have previously shown that abrogating DNAM-1 activity on CD8+ T cells results in development of milder graft-versus-host disease (GVHD) [31] , [32] . On the other hand, Seth et al reported that the absence of CD155 aggravated acute GVHD, which is mainly caused by CD4 + T cells [33] .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that abrogating DNAM-1 activity on CD8+ T cells results in development of milder graft-versus-host disease (GVHD) [31] , [32] . On the other hand, Seth et al reported that the absence of CD155 aggravated acute GVHD, which is mainly caused by CD4 + T cells [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Co-stimulation of DNAM-1 induced the exacerbation of GVHD, while blocking DNAM-1 attenuated the effects of GVHD. 91,92 It remains to be seen whether DNAM-1 drives the anti-GVHD effects of NK cells in humans.…”
Section: Dnam-1 In Immune-related Diseasesmentioning
confidence: 99%
“…Using mouse models, the role of DNAM‐1 on the surface of CD8 + T cells in GVHD was determined. Co‐stimulation of DNAM‐1 induced the exacerbation of GVHD, while blocking DNAM‐1 attenuated the effects of GVHD . It remains to be seen whether DNAM‐1 drives the anti‐GVHD effects of NK cells in humans.…”
Section: Dnam‐1 In Immune‐related Diseasesmentioning
confidence: 99%